(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2022)
Introduction: Prediabetes is considered as significant risk factor of overt diabetes. Gamma glutamyl transferase is an oxidative stress marker that is synthesized in liver. Oxidative stress causes impaired insulin secretion from beta cells of pancreas. Serum Gamma glutamyl transferase level increases in persons with diabetes and cardiovascular disease. Objective: To find out the association of serum Gamma glutamyl transferase and impaired fasting glucose. Materials and Methods: This cross-sectional analytical study was carried out among 120 subjects aged 25–55 years in the Biochemistry department of Sir Salimullah Medical College, Dhaka during the period of March 2018 to February 2019. The subjects of the study were grouped as normal fasting glucose and impaired fasting glucose as per the criterion of WHO. Blood was collected to perform OGTT. Serum was separated to measure Gamma glutamyl transferase (GGT) and lipid profile. Results: GGT levels were significantly greater (p<0.01) in impaired fasting glucose (IFG) group than normal fasting glucose (NFG) group (67.2±14.4 vs 24.2±8.4). Odds Ratio (OR) for IFG were 4.1 and 20.3 with GGT tertile 2 (24.0-42.0) U/L and tertile 3 (>42.0) U/L where T1 (< 24.0) U/L was considered as reference category. Multiple regression analysis was done to find out the relation between Fasting plasma glucose (FPG) and serum GGT by adjustment of other factors, which revealed that IFG was significantly (p< 0.01) associated with serum GGT. Conclusion: Subjects with IFG have higher serum GGT than NFG subjects and higher serum GGT level is associated with greater risk of IFG. Moreover, GGT has strong independent relationship with FPG. The association of serum GGT with IFG suggests that it can be used as adjuvant marker for risk assessment of DM and screening tool for economically underdeveloped country like Bangladesh. JAFMC Bangladesh. Vol 17, No 2 (December) 2021: 57-60